Effect of vibrational mating disruption on flight activity and oviposition to control the grapevine pest, Scaphoideustitanus. (July 2022) - Zaffaroni-Caorsi, Valentina; Nieri, Rachele; Pugno, Nicola M.; Mazzoni, Valerio
Abstract: The increasing demand for safe and sustainably produced food is leading to the development of strategies of pest control alternative to chemicals. One innovative method is Vibrational Mating Disruption (VMD) to disrupt insect communication in plants. VMD was proven effective in preventing mating of the grapevine pest Scaphoideus titanus, vector of flavescence dorée. However, the stress induced by VMD on the target species has the potential to influence other crucial aspects of the insect biology and ethology. Therefore, the goal of this study was to understand side effects of VMD on the flight activity and oviposition of S. titanus . The results of our experiments conducted in the greenhouse showed that in the presence of a receptive female, males fly more if exposed to vibrations than in the silent control but not differently from singles males in silence. Surprisingly, we found that also females subjected to VMD fly more than in the silence. Regarding oviposition, we found that mated females exposed to vibrations and single females (unmated) laid significantly fewer eggs than mated females in silence. In conclusion, this study shows the potential of VMD to interfere, besides with mating, with other important biological aspects of the pest species. Graphical abstract: Image 1 Highlights: Vibrational Mating Disruption (VMD) increases flight activity of Scaphoideus titanus males and females . VMD reduces oviposition in S. titanus. VMD could affect pest population density by interfering with multiple behaviors of target species.